1994
DOI: 10.1039/c39940002367
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the structures of iodosylbenzene (PhIO) and the related imido compound, PhINSO2-4-Me-C6H4, by X-ray powder diffraction and EXAFS (extended X-ray absorption fine structure) spectroscopy

Abstract: Structural data derived from X-ray powder diffraction and EXAFS spectroscopy are presented for iodosyl benzene (PhlO) and the imido analogue, PhlNS02-4-Me-C6H4, which indicate that these compounds are polymeric in the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 12 publications
0
61
0
2
Order By: Relevance
“…PhIO, which is polymeric in nature [84], is the classical oxygen donor in these systems, but a closely related oxidant, PhI(OAc) 2 , has been receiving considerable attention recently, as an in situ source of monomeric PhIO that reacts promptly with the Mn-porphyrin [39] with minimal formation of the PhIO disproportionation products, PhI and PhIO 2 [85]. The true nature of the coordination sphere of the Mn center at the rate-limiting step of the catalytic oxidation by different oxygen donors has been questioned by Collman et al [43], who concluded that the active species generated from PhIO and PhI(OAc) 2 were different.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…PhIO, which is polymeric in nature [84], is the classical oxygen donor in these systems, but a closely related oxidant, PhI(OAc) 2 , has been receiving considerable attention recently, as an in situ source of monomeric PhIO that reacts promptly with the Mn-porphyrin [39] with minimal formation of the PhIO disproportionation products, PhI and PhIO 2 [85]. The true nature of the coordination sphere of the Mn center at the rate-limiting step of the catalytic oxidation by different oxygen donors has been questioned by Collman et al [43], who concluded that the active species generated from PhIO and PhI(OAc) 2 were different.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
“…Commercially available iodosylbenzene (PhIO) 1 , a pale yellow amorphous powder, is a versatile oxygen atom transfer agent in organic and biomimetic syntheses 1. A µ‐oxo‐bridged polymeric structure of iodosylbenzene 1 with a secondary I ··· O hypervalent bonding of 2.377(12) Å has been deduced from X‐ray powder diffraction and extended X‐ray absorption fine structure analysis (Scheme ) 3. Hence, iodosylbenzene 1 is essentially insoluble in all nonreactive organic solvents 4,5…”
Section: Synthesis and Structure Of Activated Iodosylbenzene Monomermentioning
confidence: 99%
“…The linear O1‐I1‐O2 hypervalent bond of the aqua crown ether complex 6a is unsymmetrical, as observed in the polymeric structure of iodosylbenzene (Scheme ) 3. The hydroxy ligand in 6a is tightly bound to iodine(III), which is slightly shorter than that predicted (1.99 Å) for covalent radii, while the water ligand is loosely bound.…”
Section: Synthesis and Structure Of Activated Iodosylbenzene Monomermentioning
confidence: 99%
“…EXAFS (extended X-ray absorption fine structure) analysis has revealed that iodosylbenzene consists of a zigzag polymer structure in which monomeric Ph-IO units are linked by intermolecular non-symmetric I-O Ð Ð Ð I bridges. 6 Owing to the polymeric structure, iodosylbenzene is insoluble in all non-reactive solvents. The introduction of electronwithdrawing or donating substituents on the phenyl ring of iodosylbenzene changes the properties of the compound, influencing both the degree of association (R-Ph-IO) n and its reactivity as an oxidant.…”
Section: Introductionmentioning
confidence: 99%